2005
DOI: 10.3748/wjg.v11.i38.6031
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of a CD14 gene polymorphism on disease outcome in patients with alcoholic liver disease and chronic hepatitis C infection

Abstract: Abstract Abstract AbstractAIM: Clinical and experimental data suggest that gut-derived endotoxins are an important pathogenic factors for progression of chronic liver disease. Recently, a C-T (-159) polymorphism in the promoter region of the CD14 gene was detected and found to confer increased CD14 expression and to be associated with advanced alcoholic liver damage. Here, we investigated this polymorphism in patients with less advanced alcoholic liver disease (ALD) and chronic hepatitis C virus (HCV) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 63 publications
2
34
0
3
Order By: Relevance
“…This association was confirmed in a second smaller study which also showed that CD14 -159TT homozygotes have higher levels of the LPS-binding acute phase proteins LBP and soluble CD14 than carriers of the C allele 57. A third study also found a higher frequency of the CD14 -159TT in subjects with alcoholic cirrhosis compared with those without, but the sample size was relatively low with only 62 cases (118 controls) 58. Finally, a small genetic study from Portugal could not find an association between carriage of the CD14 -159T allele and ALD 59…”
Section: The Search For Genetic Risk Factors Of Aldmentioning
confidence: 78%
“…This association was confirmed in a second smaller study which also showed that CD14 -159TT homozygotes have higher levels of the LPS-binding acute phase proteins LBP and soluble CD14 than carriers of the C allele 57. A third study also found a higher frequency of the CD14 -159TT in subjects with alcoholic cirrhosis compared with those without, but the sample size was relatively low with only 62 cases (118 controls) 58. Finally, a small genetic study from Portugal could not find an association between carriage of the CD14 -159T allele and ALD 59…”
Section: The Search For Genetic Risk Factors Of Aldmentioning
confidence: 78%
“…Higher sCD14 levels may reflect more cells responding to LPS or a genetic predisposition towards increased LPS responsiveness. Indeed, high sCD14 levels in the setting of alcohol abuse 42 or HCV infection HCV infection 43 have been associated with a polymorphism in the promoter region of the CD14 gene (−159C/T). LPS-induced monocyte activation may increase systemic cytokine production, particularly as both circulating CD14 + CD16 + monocytes and hepatic macrophages are increased in cirrhosis 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Soluble CD14 has been associated with a variety of diseases, such as meningococcal sepsis [23] (and with severity of sepsis [33]), human immune deficiency [4], acute pancreatitis [34], recurrent middle-ear infections [31], chronic liver disease [35], Gaucher type 1 disease [36], systemic lupus erythematosus [37], and diabetes mellitus type 1 and possibly type 2 [38].…”
Section: Soluble Cd14 and Association With Diseasementioning
confidence: 99%